RELATIONSHIP BETWEEN SLEEP QUALITY AND ACADEMIC BURNOUT IN STUDENT ORGANIZERS OF STIKES KARSA HUSADA GARUT - Nugraha, Andri; Daniati, Eva; Rinjani, Santi; Hendra, Hendra (Jurnal Medika Cendikia, 2023)
Academic burnout can affect students' academic performance and emotional well-being, resulting in a decline in the quality of graduates. Quality sleep creates a feeling of freshness and well-being after waking up, while lack of sleep and poor quality can cause various physiological disorders, such as decreased immune status. Objective This study is to identify the relationship between sleep quality and academic burnout in student organizers of STIKes Karsa Husada Garut. This research method is descriptive correlation with a cross-sectional approach. the number of samples was 69 people and data analysis using the Fisher Exact Test. The results showed that there was a significant relationship between sleep quality and academic burnout in student organizers of STIKes Karsa Husada Garut with a p-value of 0.00 (P <0.05). the conclusion in this research is that there is a relationship between sleep quality and academic burnout in student organizers.